Constraints and Challenges in Implementing Text-Based Teaching in Particular Contexts - Pinilih, Murni Sekar; Tahir, Asman Bin Mohd Tahir; Susilo, Dinantari Susilo; Kusumamawarni, Deaseptia Nirmala; Suharyadi; Said, Dian Riani (International Journal of Applied Educational Research (IJAER), 2023)
This research focuses on exploring the constraints and challenges faced by teachers and students when implementing text-based teaching in specific contexts. Text-based teaching has been proven to have a significant impact on the principles of English as a Foreign Language (EFL) teaching and learning, improving students' ability to understand the meaning and fostering communication competence in authentic environments. However, despite its benefits, various obstacles and challenges hinder the successful implementation of this approach. These constraints include a lack of vocabulary and grammar acquisition, inadequate English language skills in context, low motivation, limited learning autonomy, and lack of cooperation among students. In addition, teachers also face challenges such as selecting appropriate authentic texts, modifying and adapting them to meet instructional objectives, designing appropriate tasks, and overcoming potential student boredom with routine activities. To overcome these barriers, teachers need to engage in comprehensive professional development to acquire the knowledge and skills necessary for effective implementation of text-based teaching. In addition, policymakers are encouraged to provide advanced training opportunities in this area, allowing teachers to improve their teaching practices.